2004
DOI: 10.1098/rspb.2003.2569
|View full text |Cite
|
Sign up to set email alerts
|

Tropical winter habitat limits reproductive success on the temperate breeding grounds in a migratory bird

Abstract: Identifying the factors that control population dynamics in migratory animals has been constrained by our inability to track individuals throughout the annual cycle. Using stable carbon isotopes, we show that the reproductive success of a long-distance migratory bird is influenced by the quality of habitat located thousands of kilometres away on tropical wintering grounds. For male American redstarts (Setophaga ruticilla), winter habitat quality influenced arrival date on the breeding grounds, which in turn af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
561
3
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 568 publications
(587 citation statements)
references
References 42 publications
20
561
3
3
Order By: Relevance
“…To conclude, we have demonstrated that despite the potential for impacts of climate change on wintering grounds to carry over and affect reproductive decisions [26], when averaged across a range of long-distance migrants the rsbl.royalsocietypublishing.org Biol Lett 9: 20130669 magnitude of such effects appears small relative to the influence of climate on breeding grounds. However, if future climate change degrades overwintering conditions more than those on breeding grounds, then carry-over effects could become more important through time.…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, we have demonstrated that despite the potential for impacts of climate change on wintering grounds to carry over and affect reproductive decisions [26], when averaged across a range of long-distance migrants the rsbl.royalsocietypublishing.org Biol Lett 9: 20130669 magnitude of such effects appears small relative to the influence of climate on breeding grounds. However, if future climate change degrades overwintering conditions more than those on breeding grounds, then carry-over effects could become more important through time.…”
Section: Discussionmentioning
confidence: 99%
“…The contrasting rates of fuel deposition in Tennessee Warblers, for example, suggest that birds fueling in shade coffee must either stay longer than those in forest or depart the study site with less energy. Either way, this implies that the temporal (time spent at stopovers) and/ or the spatial (number and location of stopover sites) organization of migration can vary with stopover habitat, with likely fitness costs mediated through carry-over effects (Norris et al 2004, Harrison et al 2011. It was previously shown that Gray-cheeked Thrush stopping over for 12-14 days in the SNSM accumulate sufficient energy reserves to undertake a migratory flight > 2500 km, allowing them to overfly the Caribbean Sea to the southern United States (Bayly et al 2013).…”
Section: Habitat Quality and Migration Strategymentioning
confidence: 99%
“…Stable-carbon isotopes (d 13 C) values of redstarts indicate the type of habitat occupied during the non-breeding season (Marra et al 1998) and signatures in red-blood cells of individuals upon arrival at the breeding grounds can be used as an indicator of the winter habitat quality. Using path analysis, Norris et al (2004) found that G1 s.d. change in d 13 C values was equivalent to G1 s.d.…”
Section: Predicting Carry-over Effects D R Norris and C M Taylor 149mentioning
confidence: 99%